2014
DOI: 10.1007/s10147-014-0774-3
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic surgery in management of oropharyngeal cancers: a preliminary experience at a tertiary cancer centre in India

Abstract: TORS is a safe, feasible, minimally invasive procedure in patients with oropharyngeal cancers. It has the least morbidity and offers benefits in terms of avoidance of tracheostomy tube, prolonged Ryle's tube and gastrostomy dependency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In a third early series of 45 cases, which mostly included tonguebase cancer, 14 patients left the operating theatre with a tracheotomy [17] . In more recent series, the percentage of tracheotomies is lower (4 of 26) [18] or even null [19] , although for the same locations (e.g. supraglottis) there are still large variations that include "always" [20] or "never" [21] .…”
Section: Discussionmentioning
confidence: 93%
“…In a third early series of 45 cases, which mostly included tonguebase cancer, 14 patients left the operating theatre with a tracheotomy [17] . In more recent series, the percentage of tracheotomies is lower (4 of 26) [18] or even null [19] , although for the same locations (e.g. supraglottis) there are still large variations that include "always" [20] or "never" [21] .…”
Section: Discussionmentioning
confidence: 93%
“…In these case series, resection beds were allowed to granulate and heal by secondary intention. [5][6][7][8][9] Genden et al 10 reported a series of 31 patients with OPSCC who underwent TORS and described the use of a musculomucosal advancement flap pharyngoplasty in 25 of these patients, with radial forearm free flap in the remaining six patients. However, they stated that four of these six patients were salvage candidates.…”
Section: Need For Free Flap Reconstructionmentioning
confidence: 99%
“…The postoperative hospital length of stay (LOS) after TORS with or without neck dissection for OPSCC ranged from 1.0 days to 14.6 days, with all but one study reporting LOS in the range of 1.0-4.3 days. [5][6][7][8][9][11][12][13] Studies comparing LOS following TORS with that following mandibulotomy for similar oropharyngeal lesions consistently report significantly shorter LOS with TORS, whether in the primary or salvage setting. 5,8 Some part of this decreased LOS may be related to decreased need for free flap reconstruction, which typically necessitates intensive postoperative monitoring for longer periods of time, while part of it may be related to decreased time to oral intake, as discussed in subsequent sections.…”
Section: Hospital Length Of Staymentioning
confidence: 99%
See 2 more Smart Citations